Ultrasonographic Imaging of Reproductive Organs Post Artificial Insemination in Aceh Cows - Juli Melia; Salsabila Putroe Wieka; Gholib Gholib; Tongku Nizwan Siregar; Ginta Riady; Nabilah Putroe Agung; Nurliana Nurliana (Jurnal Agripet, 2026)
This study aimed to describe the condition of the reproductive organs of Aceh cattle after artificial insemination (AI) and identify the causes of fertilization failure using transrectal ultrasonography. The study involved six Aceh cattle. Ultrasonographic examinations were conducted on days 25 and 35 post-AI to observe endometrial thickness, corpus luteum (CL) presence, and embryos. The results showed that two cows (cows 1 and 2) were detected as pregnant, indicated by the presence of embryonic vesicles and CL on both observation days. One cow (cow 3) showed an embryonic vesicle and CL on day 25, but these were no longer observed on day 35, suggesting early embryonic mortality. The remaining three cows (cows 4, 5, and 6) were not detected to be pregnant. The average CL size in pregnant cow 1 was 1.20±0.00 cm on day 25 and 1.30±0.00 cm on day 35, which was larger than that of pregnant cow 2 (0.90±0.14 cm and 1.00±0.00 cm, respectively). The average endometrial diameter in pregnant cow 1 was also greater (2.25±0.14 cm and 4.20±0.21 cm) than that in pregnant cow 2 (1.10±0.28 cm and 1.95±0.56 cm) and the non-pregnant cow (1.15±0.05 cm and 2.45±0.26 cm). In conclusion, CL size and endometrial thickness differed between pregnant and non-pregnant Aceh cows. Fertilization failure in Aceh cattle may be associated with early embryonic death, endometritis, ovarian cysts, and factors related to reproductive management.